Fibroblast growth factor 21 predicts arteriovenous fistula functional patency loss and mortality in patients undergoing maintenance hemodialysis - Xinhui Hu; Hong Ding; Qing Wei; Ruoxin Chen; Weiting Zhao; Liqiong Jiang; Jing Wang; Haifei Liu; Jingyuan Cao; Hong Liu; Bin Wang (Renal Failure)
Background Arteriovenous fistula (AVF) dysfunction is a common complication in patients undergoing maintenance hemodialysis (MHD). Elevated serum levels of fibroblast growth factor 21 (FGF21) are associated with atherosclerosis and cardiovascular mortality. However, its association with vascular access outcomes remains elusive. The present study evaluated the relationship of serum FGF21 levels with AVF dysfunction and all-cause mortality in patients undergoing MHD.Methods We included patients undergoing MHD using AVF from January 2018 to December 2019. FGF21 concentration was detected using enzyme-linked immunosorbent assay. Patients were followed up to record two clinical outcomes, AVF functional patency loss and all-cause mortality. The follow-up period ended on April 30, 2022.Results Among 147 patients, the mean age was 58.49 ± 14.41 years, and the median serum level of FGF21 was 150.15 (70.57–318.01) pg/mL. During the median follow-up period of 40.83 months, the serum level of FGF21 was an independent risk factor for AVF functional patency loss (per 1 pg/mL increase, HR 1.002 [95% CI: 1.001–1.003, p = 0.003]). Patients with higher serum levels of FGF21 were more likely to suffer from all-cause mortality (per 1 pg/mL increase, HR 1.002 [95% CI: 1.000–1.003, p = 0.014]). The optimal cutoffs for FGF21 to predict AVF functional patency loss and all-cause mortality in patients undergoing MHD were 149.98 pg/mL and 146.43 pg/mL, with AUCs of 0.701 (95% CI: 0.606–0.796, p < 0.001) and 0.677 (95% CI: 0.595–0.752, p = 0.002), respectively.Conclusions Serum FGF21 levels were an independent risk factor and predictor for AVF functional patency loss and all-cause mortality in patients undergoing MHD.